(untitled) (Fiep Bulletin - online, 2014)
Improper physical development is influenced by both endogenous and exogenous factors. The family plays a very specific role, because it presents a potential of healthy physical development in terms of biological and social influence. The objective of the research was to find a relation between the body mass indexes (BMI ) of parents and their children. The research sample involved pupils of the sixth (n-152) grade of elementary schools, second grade students of higher secondary schools (n-147) and their parents from three regions of Slovakia. The results of correlation analysis proved significant relations between parent-child BMI in all age groups, except for 12-year old girls, more significantly between parents and their sons. The results of multiple correlation analysis proved that the BMI variability in children is significantly determined by the variability of monitored parameters of both parents with certain sex-based differences, closer in sons (p<0.01) than in daughters (p<0.05).